HOME CARE IN THE REPUBLIC OF MOLDOVA: THE CHALLENGES FOR HEALTH AND SOCIAL POLICIES - CHEIANU-ANDREI, Diana (Economy and Sociology, 2021)
Home care responds to people’s health and social needs by offering quality services at the recipient’s residence. Demand for these services is steadily increasing, especially due to the aging population. The purpuse of this study is to analyze the situation in the field of home care in the Republic of Moldova. The study is based on a methodological approach focused on the analysis of the normative framework, the opinions of the service providers (public and private), but also of the representatives of the local public authorities, including the beneficiaries. Quantitative and qualitative research methods have been used. Sociological survey based on a questionnaire was applied to 84 home care providers from 23 out of 35 Moldovan administrative territorial units. In-depth individual interviews were conducted with 2 categories of people: 20 home care beneficiaries and 24 mayors. The results of the assessment reveal shortcomings and achievements in the field of home care in the Republic of Moldova and gives recommendations for governmental and local authorities, public and private providers in order to develop home care services and policies in the field of home care, organization of advocacy activities.